Rare earth manganese zirconium composite compound doped at grain boundary and surface, its manufacturing method and use

JP2025505106AActive Publication Date: 2025-02-21GUOKE RE ADVANCED MATERIALS CO LTD +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024542103
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-14
Filing Date
2023-02-13
Publication Date
2025-02-21
Estimated Expiration
2043-02-13

AI Technical Summary

Benefits of technology

【0024】 要約すると、本発明は粒界及び表面にドーピングされた希土類マンガンジルコニウム複合化合物、その製造方法及び用途を提供し、ドーピング法により希土類、マンガン、遷移金属等の元素を希土類ジルコニウム系酸化物の表面、粒界及び結晶粒内部に添加し、ペロブスカイト、スピネル、ムライト等の構造を含有する希土類マンガンジルコニウム複合化合物を得、一方で希土類、マンガン、遷移金属等の元素で形成された化合物は高温時に希土類ジルコニウム系酸化物によってその相構造変換を抑制し、その高温触媒活性を向上させ、他方で表面、粒界における希土類ジルコニウム系酸化物の自由活性酸素が活性点に拡散しやすく、希土類マンガンジルコニウム複合化合物の触媒活性をさらに向上させる。本発明の技術案は粒界と表面のドーピングによって表面、粒界における金属イオンの酸化能力を大幅に向上させ、活性成分の高温焼結失活を抑制し、且つNOの触媒酸化能力を向上させる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025505106000001_ABST
    Figure 2025505106000001_ABST
Patent Text Reader

Abstract

The present invention relates to a rare earth manganese zirconium composite compound doped on the grain boundary and surface, its preparation method and application. A rare earth manganese oxide with a special structure is formed on the grain boundary and surface of the rare earth zirconium oxide by the grain boundary doping method, and oxygen defects on the grain boundary and surface are increased, thereby increasing the amount of active oxygen, improving the catalytic activity of the rare earth manganese zirconium composite compound, suppressing its high-temperature sintering, and improving its ability to catalytically oxidize NO. The use of this rare earth manganese zirconium composite compound as a catalyst can greatly reduce the amount of precious metals used.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] <CROSS REFERENCE TO RELATED APPLICATIONS> This application is filed based on a Chinese patent application having application number 202210135508.7 and filing date of February 14, 2022, and claims priority to the Chinese patent application, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to the technical field of rare earth manganese zirconium composite compounds, and more particularly to a rare earth manganese zirconium composite compound doped at grain boundaries and on the surface, and its preparation method and use. [Background technology]

[0003] Lean-burn engines (e.g. diesel engines and lean-burn gasoline engines) are widely used due to their fuel efficiency and low greenhouse gas emissions. However, they produce a large amount of nitrogen oxides (NO x ) not only causes significant environmental problems such as photochemical smog and acid rain, but also seriously harms human health. Therefore, NO in the exhaust gas of lean-burn engines x How to effectively remove nitrogen oxides (NO) from diesel engines is a hot topic of research both at home and abroad. DOC is a diesel engine oxidation catalyst. x DOCs are used to reduce the pollutants of CO, hydrocarbons (HC) and carbon monoxide (CO). Currently, DOCs usually use alumina-supported precious metals to oxidize HC, CO and some NO, but the NO→NO2 oxidation rate is usually less than 40%. To achieve higher NO oxidation performance, more precious metals must be applied, which significantly increases catalyst costs. Metal oxide catalysts are not only low-cost but also have relatively high catalytic activity, and have attracted attention in recent years. Examples of such catalysts include Cu-Cr(Co), MnO x-CeO2 and CuMnO4 composite oxides are beneficial for diesel carbon smoke and NO oxidation, but metal oxides generally have poor temperature resistance and are easily deactivated at high temperatures. Therefore, there is an urgent need to develop new catalytic materials with relatively high NO catalytic activity and high temperature stability. Summary of the Invention [Problem to be solved by the invention]

[0004] Based on the above-mentioned situation of the prior art, the object of the present invention is to provide a rare earth manganese zirconium composite compound doped on the grain boundary and surface, and its preparation method and use, which can greatly improve the oxidation ability of metal ions on the surface and grain boundary by doping, suppress the high-temperature sintering deactivation of active components, and improve the catalytic oxidation ability of NO. [Means for solving the problem]

[0005] In order to achieve the above object, according to one aspect of the present invention, there is provided a rare earth manganese zirconium composite compound doped on grain boundaries and surfaces, the rare earth manganese zirconium composite compound having a chemical formula of RE a Mn b Zr c L d M e O (2-δ) D β where RE is a rare earth element, M, L are cation doping elements, and D is an anion doping element; Here, 0.1≦a≦0.5, 0.05≦b≦0.4, 0.2≦c≦0.8, 0≦d≦0.2, 0≦e≦0.2, 0≦δ≦0.1, 0≦β≦0.1, and a+b+c+d+e=1.

[0006] Furthermore, the grain boundaries and the surface of said rare earth manganese zirconium composite compound contain one or more of the doping elements M, L and D.

[0007] Furthermore, the doping elements M, L and D are in the form of one or more of oxides, nitrogen-containing compounds, fluorine compounds, phosphates and sulfates at the grain boundaries and surface of the rare earth manganese zirconium composite oxide.

[0008] Further, the RE comprises one or a combination of one or more of La, Ce, Pr, Nd, Sm, Eu, Gd, Ho, Er, Tm, Yb, Lu, Y, and Sc; Preferably, RE is one or a combination of one or more of La, Ce, Pr, Nd, Sm, Eu, Gd and Y.

[0009] Furthermore, the doping element M of the cations is a transition metal, preferably one or a combination of one or more of Fe, Co, Ni, Cu, Zn, V, Ti, Cr, Mo, W, Hf and Nb; the doping element L of the cations is one or a combination of one or more of alkaline earth metals and Ga, Al, Si, Sn, preferably the alkaline earth metal is one or a combination of one or more of Ba, Sr, Mg and Ca; and the doping element D comprises one or a combination of one or more of the anions N, P, F and S.

[0010] Furthermore, the ratio of the sum of +3 and +4 valences of Mn on the surface and grain boundaries of the rare earth manganese zirconium composite compound to the total valence of Mn is greater than 80%, preferably greater than 90%.

[0011] Furthermore, the rare earth manganese zirconium composite compound doped on the grain boundary and surface has a core-shell structure, the core includes rare earth and zirconium elements, and the shell includes rare earth and manganese elements. The present invention designs the type and content of the shell and / or core elements based on the theoretically calculated difference between the element surface energy and the oxygen vacancy formation energy, thereby comprehensively improving the thermal stability and oxygen storage and release performance of the rare earth manganese zirconium composite oxide.

[0012] Furthermore, the rare earth manganese zirconium composite compound doped on the grain boundary and surface includes a rare earth zirconium-based oxide with an element gradient distribution structure. The present invention designs the type and content of elements in the gradient structure based on the theoretically calculated difference between the element surface energy and the oxygen vacancy formation energy, and gradually increases or decreases the content of a specific element from the inside to the outside in the radial direction of the crystal grain, thereby comprehensively improving the thermal stability and oxygen storage and release performance of the rare earth manganese zirconium composite oxide.

[0013] According to a second aspect of the present invention, there is provided a method for producing a grain boundary and surface doped rare earth manganese zirconium composite compound according to the first aspect of the present invention, comprising: Step S1: mixing an aqueous mixed salt solution of Zr and RE or an aqueous mixed salt solution of Zr, RE, L and D having a desired stoichiometric ratio with an alkaline solution, carrying out a precipitation reaction, and then filtering, washing, drying and roasting to obtain a rare earth zirconium oxide containing RE and L; Step S2 of mixing a required stoichiometric mixed salt aqueous solution of Mn and RE or a mixed salt aqueous solution of Mn, RE, M and D with the rare earth zirconium oxide obtained in step S1 to obtain a composite compound wet material; Step S3, which performs one or two heat treatments on the composite compound moisture-retaining material obtained in step S2; and Step S4, which performs one or two post-sintering treatments on the material obtained in Step S3 to obtain a rare earth manganese zirconium composite compound doped at grain boundaries and on the surface.

[0014] Furthermore, the doping element D is added in one or two steps in steps S1 and S2, and the doping element D is added as one or a combination of one or more of nitrates, fluorine compounds, phosphates, and sulfates, and preferably as one or a combination of one or more of nitrates and sulfates.

[0015] Furthermore, the manganese source in the mixed salt aqueous solution in steps S1 and S2 includes one or a combination of one or more of chlorides, nitrates, sulfates, and acetates, and is preferably manganese nitrate; the zirconium source includes one or a combination of one or more of oxychlorides, nitrates, sulfates, acetates, and citrates, and is preferably zirconium oxynitrate; and the M, L, and RE salt aqueous solutions include one or a combination of one or more of chlorides, nitrates, sulfates, acetates, citrates, and liquid salts of amino acids, and organosilicon compounds, and is preferably nitrates.

[0016] Furthermore, the alkaline solution in step S1 contains at least one of magnesium hydrogen carbonate, urea, and hydroxide, carbonate, and hydrogen carbonate of at least one element of ammonium, sodium, and potassium, and is preferably at least one of sodium hydroxide, urea, ammonia water, and ammonium hydrogen carbonate.

[0017] Furthermore, in the precipitation process of step S1, the pH value is controlled to be 4.5 to 14, preferably 5 to 11, the pH value at the end of the precipitation is controlled to be 8 to 13, preferably 9 to 11, and the temperature in the precipitation process is 0 to 120°C, preferably 20 to 80°C.

[0018] Furthermore, the roasting temperature of the rare earth zirconium oxide in step S1 is 500 to 1000° C. and the roasting time is 1 to 20 hours, and preferably, the roasting temperature is 600 to 900° C. and the roasting time is 2 to 10 hours.

[0019] Furthermore, the heat treatment temperature in step S3 is 100 to 500° C. and the time is 2 to 30 hours, and preferably, the heat treatment temperature is 150 to 300° C. and the time is 6 to 12 hours.

[0020] Furthermore, the firing temperature in step S4 is 400 to 1000° C. and the firing time is 1 to 20 hours, and preferably, the firing temperature is 500 to 900° C. and the firing time is 3 to 10 hours.

[0021] Furthermore, the particle size D50 of the post-treatment of said rare earth manganese zirconium composite compound is less than 15um, preferably the particle size D50 is less than 10um.

[0022] Furthermore, rare earth manganese oxide containing a perovskite, spinel or mullite structure is formed on the surface and grain boundaries of the rare earth zirconium oxide after firing.

[0023] According to a third aspect of the present invention, there is provided a use of the grain boundary and surface doped rare earth manganese zirconium composite compound according to the first aspect of the present invention in the fields of automobile exhaust gas purification, industrial exhaust gas treatment and catalytic combustion. Effect of the Invention

[0024] In summary, the present invention provides a rare earth manganese zirconium composite compound doped with grain boundary and surface, its preparation method and use, and doping rare earth, manganese, transition metal and other elements into the surface, grain boundary and inside of crystal grain of rare earth zirconium oxide to obtain rare earth manganese zirconium composite compound with perovskite, spinel, mullite and other structures; on the one hand, the compound formed by rare earth, manganese, transition metal and other elements is inhibited by rare earth zirconium oxide at high temperature to transform its phase structure, improving its high-temperature catalytic activity; on the other hand, the free active oxygen of rare earth zirconium oxide on the surface and grain boundary is easily diffused to the active site, further improving the catalytic activity of rare earth manganese zirconium composite compound. The technical solution of the present invention greatly improves the oxidation ability of metal ions on the surface and grain boundary by doping grain boundary and surface, inhibits high-temperature sintering deactivation of active components, and improves the catalytic oxidation ability of NO. [Brief description of the drawings]

[0025] [Figure 1] 1 is a flow chart of a method for producing a surface and grain boundary doped rare earth manganese zirconium composite compound according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] In order to make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be described in more detail below with reference to the drawings in conjunction with specific embodiments. It should be understood that these descriptions are illustrative and do not limit the scope of the present invention. In addition, in the following description, descriptions of known structures and techniques are omitted to avoid unnecessary confusion of the concept of the present invention.

[0027] According to a first aspect of the present invention, there is provided a rare earth manganese zirconium composite compound doped at grain boundaries and surfaces, the rare earth manganese zirconium composite compound having a chemical formula of RE a Mn b Zr c L d M e O (2-δ) D β where RE is a rare earth element, M, L are cationic doping elements, and D is an anionic doping element, where the value of each element may be 0.1≦a≦0.5, 0.05≦b≦0.4, 0.2≦c≦0.8, 0≦d≦0.2, 0≦e≦0.2, 0≦δ≦0.1, 0≦β≦0.1, and a+b+c+d+e=1.

[0028] Here, the element RE may be one or a combination of one or more of La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y and Sc, and preferably, RE is one or a combination of one or more of La, Ce, Pr, Nd, Sm, Eu, Gd and Y; the doping element M is a transition metal, and preferably is one or a combination of one or more of Fe, Co, Ni, Cu, Zn, V, Ti, Cr, Mo, W, Hf and Nb; the molar ratio of the M element in the grain boundary and on the surface is 10% to 70%; and the doping element L may be one or more combinations of alkaline earth metals and Ga, Al, Si, Sn, the alkaline earth metals are preferably one or more combinations of Ba, Sr, Mg, and Ca, the molar ratio of L element at grain boundary and surface is 10%-70%, the doping element D may be one or more combinations of anions N, P, F, and S, the molar ratio of D element at grain boundary and surface is 10%-70%. The morphology and ratio of L, M, and D at grain boundary and surface are adjusted and controlled by controlling the precipitation parameters, heat treatment temperature and roasting temperature, time, atmosphere, etc. of the product.

[0029] The rare earth manganese zirconium composite compound contains one or more of doping elements M, L and D at the grain boundaries and on the surface.

[0030] The doping elements M, L and D are in the form of one or more of oxides, nitrogen-containing compounds, fluorides, phosphates and sulfates at the grain boundaries and surface of the rare earth manganese zirconium composite oxide.

[0031] The proportion of the sum of +3 and +4 valences of element Mn on the surface and grain boundaries of the rare earth manganese zirconium composite compound to the total valence of Mn is greater than 80%, preferably greater than 90%.

[0032] The rare earth manganese zirconium composite oxide provided by the embodiment of the present invention has a core-shell structure, the core includes rare earth and zirconium elements, and the shell includes rare earth and manganese elements. For other features and advantages of the core-shell structure of the rare earth manganese zirconium composite oxide, please refer to the Chinese patent application with application number ZL201910833257.8 filed on September 4, 2019 and the invention title "Core-shell structure rare earth manganese / cerium zirconium composite compound, preparation method and catalyst" and its entire content description. The present invention designs the type and content of shell and / or core elements based on the theoretically calculated difference between the element surface energy and the oxygen vacancy formation energy, and comprehensively improves the thermal stability and oxygen storage and release performance of the rare earth manganese zirconium composite oxide.

[0033] The rare earth manganese zirconium composite oxide provided in the embodiment of the present invention includes a rare earth zirconium-based oxide with an element gradient distribution structure. For other features and advantages of the element gradient distribution structure of the rare earth zirconium-based oxide, please refer to the Chinese patent application with application number CN202010982979.2, filed on September 17, 2020, and the invention title "Cerium zirconium composite oxide with element gradient distribution and its manufacturing method" and its entire content description. Based on the theoretically calculated difference between the element surface energy and the oxygen vacancy formation energy, the present invention designs and controls the element types and contents in the gradient structure, and gradually increases or decreases the content of a specific element from the inside to the outside in the radial direction of the crystal grain, thereby comprehensively improving the thermal stability and oxygen storage and release performance of the rare earth manganese zirconium composite oxide.

[0034] According to a second aspect of the present invention, there is provided a method for producing the surface and grain boundary doped rare earth manganese zirconium composite compound according to the first aspect of the present invention, and FIG. 1 shows a flow chart of the method, which includes steps S1 to S4.

[0035] In step S1, a mixed salt aqueous solution of Zr and RE or a mixed salt aqueous solution of Zr, RE and L with a desired stoichiometric ratio is mixed with an alkaline solution, a precipitation reaction is carried out, and then, after filtration, washing, drying and roasting, a rare earth zirconium oxide containing RE and L is obtained, where the pH value in the precipitation process is controlled to 4.5-14, preferably 5-11, the pH value at the end of the precipitation is controlled to 8-13, preferably 9-11, and the temperature in the precipitation process is 0-120°C, preferably 20-80°C. The roasting conditions are to hold within a range of 500-1000°C for 1-20 hours, preferably within a range of 600°C-900°C for 2-10 hours, and in step S1, a doping element D is added, and the doping element D is added as one or a combination of one or more of, for example, nitrates, fluorine compounds, phosphates and sulfates, preferably one or a combination of one or more of nitrates and sulfates. The alkaline solution may be at least one of magnesium hydrogen carbonate, urea, and hydroxide, carbonate, and hydrogen carbonate of at least one element of ammonium, sodium, and potassium, and is preferably at least one of sodium hydroxide, urea, ammonia water, and ammonium hydrogen carbonate.

[0036] In step S2, the mixed salt aqueous solution of Mn and RE or the mixed salt aqueous solution of Mn, RE and M with the rare earth zirconium oxide obtained in step S1 is mixed to obtain a composite compound wet material, and in step S2, a doping element D may be added, for example, the doping element D is added in the form of one or a combination of one or more of nitrates, fluorine compounds, phosphates and sulfates, and preferably in the form of one or a combination of one or more of nitrates and sulfates.

[0037] The manganese source in the mixed salt solution in steps S1 and S2 includes one or a combination of one or more of chlorides, nitrates, sulfates, and acetates, and is preferably manganese nitrate; the zirconium source includes one or a combination of one or more of oxychlorides, nitrates, sulfates, acetates, and citrates, and is preferably zirconium oxynitrate; and the M, L, and RE salt solutions include one or a combination of one or more of chlorides, nitrates, sulfates, acetates, citrates, and liquid salts of amino acids, and organosilicon compounds, and is preferably nitrates.

[0038] In S3, the composite compound humidifier obtained in step S2 is heat-treated once or twice, the heat-treatment temperature is, for example, 100-500°C, and the time is 2-30h, preferably, the heat-treatment temperature is 150-300°C, and the time is 6-12h. In order to meet the special requirements of the rare earth manganese zirconium composite compound for different applications, it is necessary to adjust or change the type of doping element and the microstructure structure in the grain boundary, and therefore it is necessary to adopt different heat-treatment regimes, for example, to carry out heat treatment in stages, so that the doping element can be more uniformly and stably introduced into the grain boundary, and treatments such as water washing and water quenching can be carried out between the two heat-treatment stages.

[0039] In S4, the material obtained in step S3 is subjected to one or two post-sintering treatments to obtain a rare earth manganese zirconium composite compound doped on the grain boundary and surface, and the sintering conditions are maintained within a range of 400 to 1000°C for 1 to 20 hours, and preferably within a range of 500 to 900°C for 3 to 10 hours. The obtained rare earth manganese zirconium composite compound is sintered once or twice to obtain a rare earth manganese zirconium composite compound powder material of a specific structure, and after sintering once, it is crushed and surface treated to avoid two sintering agglomerations.

[0040] The particle size D50 of the rare earth manganese zirconium composite compound after treatment is less than 15um, preferably less than 10um. In this manufacturing method, rare earth, manganese, transition metals and other elements are added to the surface and grain boundary of rare earth zirconium oxide by doping to obtain rare earth manganese zirconium composite compound containing perovskite, spinel, mullite and other structures, thereby improving the oxygen vacancy concentration of oxygen vacancies on the surface and grain boundary, and increasing the amount of free active oxygen. The element gradient distribution structure or core-shell structure can improve the perovskite, spinel, mullite and other structures on the surface grain boundary, improve its high-temperature catalytic activity, suppress its high-temperature sintering, and at the same time reduce the amount of precious metal used in the catalyst.

[0041] According to the third aspect of the present invention, there is provided the use of the rare earth manganese zirconium composite compound doped on the grain boundary and the surface as described in the first aspect of the present invention in the fields of automobile exhaust gas purification, industrial exhaust gas treatment, catalytic combustion, etc. The rare earth manganese zirconium composite compound provided by the embodiment of the present invention is doped to greatly increase the amount of free active oxygen on the surface and grain boundary, which is favorable for the catalytic oxidation of NO molecules. It has good effects in terms of suppressing high-temperature sintering deactivation and reducing the amount of precious metals, and can significantly improve the catalytic oxidation ability of NO when applied in the fields of automobile exhaust gas purification, industrial exhaust gas treatment, and catalytic combustion.

[0042] The present invention will be further described below by specific examples, and the catalytic performance of the prepared rare earth manganese zirconium composite compound for the oxidation of NO is measured. The catalytic performance test conditions of each example are the same, and the specific test steps are as follows: 50 mg of the prepared rare earth manganese zirconium composite compound is taken and put into a microreactor to carry out the catalytic activity evaluation test, and the NO, NO2 and NO are measured at the corresponding temperature by an infrared gas analyzer (MKS). xThe content of is recorded, and the conversion rate of NO is calculated based on the results. The specific test conditions are as follows: the volume of the reaction gas is 10% oxygen, 10% water, 300 ppm carbon monoxide, 300 ppm nitrogen monoxide, and 300 ppm CH6; the equilibrium gas is nitrogen gas; the total flow rate is 150 mL / min; and the space velocity is 40,000 h -1 The reaction temperature was set to increase from room temperature to 400° C. at a rate of 20° C. / min, and the reaction time was 20 min.

[0043] Comparative Example 1 Ce 0.05 Nd 0.05 Mn 0.05 Zr 0.8 The molar ratio of Ce / Mn / Nd / Zr in the O2 rare earth zirconium manganese composite oxide was mixed to be 1:1:1:16, and a mixed solution with a total cation concentration of 1.5M was obtained. Under stirring conditions, the mixed material liquid was added to a 3.0M NaOH solution at a constant speed, the pH during precipitation was 10-14, and the final pH value was 10. The temperature was controlled at 50°C, and the precipitate was filtered, washed, dried, and roasted at 650°C for 8h to obtain the rare earth manganese zirconium composite compound Ce doped in the bulk phase. 0.05 Nd 0.05 Mn 0.05 Zr 0.8 Got O2.

[0044] The catalytic oxidation of the rare earth manganese zirconium composite compound obtained by the manufacturing method of Comparative Example 1 had a maximum NO conversion of 42%, and the corresponding conversion temperature was 357° C. After aging at a high temperature of 850° C. for 15 hours, the maximum NO conversion was 30%, and the corresponding conversion temperature was 380° C.

[0045] Comparative Example 2 Ce 0.1 Al 0.1 Mn 0.2 Zr 0.6The molar ratio of Ce / Al / Mn / Zr in the O2 rare earth zirconium manganese composite oxide was mixed to be 1:1:2:6 to obtain a mixed solution with a concentration of 1.0M. Under stirring conditions, the mixed material liquid and 2.8M NaOH solution were added into the reactor at a constant speed, the pH during precipitation was controlled to 9±0.2, the final pH value was 9.2, and the temperature was controlled at 40°C. The precipitate was filtered, washed, dried, and roasted at 600°C for 10h to obtain the rare earth manganese zirconium composite compound Ce doped in the bulk phase. 0.1 Al 0.1 Mn 0.2 Zr 0.6 Got O2.

[0046] The maximum conversion rate of NO oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the production method of Comparative Example 2 was 45%, and the conversion temperature corresponding to the maximum conversion rate was 352°C.

[0047] Comparative Example 3 Ce 0.2 La 0.1 Mn 0.1 Fe 0.1 Zr 0.5 The molar ratio of Ce / La / Mn / Fe / Zr in the O2 rare earth zirconium manganese composite oxide is 2:1:1:1:5, where the types of cerium salt and lanthanum salt are acetate salts, and a mixed solution with a concentration of 1.0M is obtained. Under stirring conditions, 2.6M ammonia aqueous solution is added to the mixed material liquid at a constant speed, the pH during precipitation is controlled to 5-9, the final pH value is 8.9, and the temperature is controlled at 60°C. The precipitate is filtered, washed, dried, and roasted at 900°C for 9h to obtain the rare earth manganese zirconium composite compound Ce doped in the bulk phase. 0.2 La 0.1 Mn 0.1 Fe 0.1 Zr 0.5 Got O2.

[0048] The maximum conversion rate of NO oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the production method of Comparative Example 2 was 49%, and the conversion temperature corresponding to the maximum conversion rate was 350°C.

[0049] Example 1 Ce 0.05 Nd 0.05 Mn 0.05 Zr 0.8 The molar ratio of Ce / Nd / Zr in the O2 rare earth zirconium manganese composite oxide was mixed to be 0.5:1:16 to obtain a mixed solution with a concentration of 1.5M. Under stirring conditions, the mixed material liquid was added to a 3.0M NaOH solution at a constant speed, the pH during precipitation was 10-14, the final pH value was 10, the temperature was controlled at 50°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 800°C for 7h to obtain a rare earth zirconium oxide. The rare earth zirconium oxide was mixed with a 4.8M Ce-containing Mn(NO3)2 solution, followed by heat treatment at 150°C for 5h and further roasting at 650°C for 8h to obtain a rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.05 Nd 0.05 Mn 0.05 Zr 0.8 Got O2.

[0050] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 52%, and the conversion temperature corresponding to the maximum conversion rate was 300°C.

[0051] Example 2 Ce 0.1 Al 0.1 Mn 0.2 Zr 0.6 The molar ratio of Ce / Al / Zr in the O2 rare earth zirconium manganese composite oxide was mixed to 0.5:1:6 to obtain a mixed solution with a concentration of 1.0M. Under stirring conditions, the mixed material liquid and 2.8M NaOH solution were added to the reactor at a constant rate, the pH during precipitation was controlled to 9±0.2, the final pH value was 9.2, and the temperature was controlled at 40°C. The precipitate was filtered, washed and dried, and the dried product was roasted at 700°C for 5h to obtain rare earth zirconium oxide. The rare earth zirconium oxide was mixed with 4.5M Ce-containing Mn(NO3)2 solution, followed by heat treatment at 170°C for 10h and roasting at 600°C for 10h to obtain rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.1Al 0.1 Mn 0.2 Zr 0.6 Got O2.

[0052] The maximum conversion rate of NO oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 55%, and the conversion temperature corresponding to the maximum conversion rate was 308°C.

[0053] Example 3 Ce 0.05 Y 0.05 Mn 0.2 Zr 0.7 The molar ratio of Ce / Y / Zr in the O2 rare earth zirconium manganese composite oxide was mixed to 0.5:0.2:7 to obtain a mixed solution with a concentration of 1.2M. Under stirring conditions, 2.6M urea solution was added to the mixed material liquid at a constant speed, the pH during precipitation was 3-9, the final pH value was 9, the temperature was controlled at 110°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 600°C for 4h to obtain rare earth zirconium oxide. The rare earth zirconium oxide was mixed with a 4.3M Y-containing MnCl2 solution, followed by heat treatment at 190°C for 6h and further roasting at 800°C for 7h to obtain rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.05 Y 0.05 Mn 0.2 Zr 0.7 Got O2.

[0054] The maximum conversion rate of NO oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 57%, and the conversion temperature corresponding to the maximum conversion rate was 306°C.

[0055] Example 4 Ce 0.2 Nd 0.05 S 0.05 Mn 0.2 Zr 0.5The molar ratio of Ce / Nd / Si / Zr in the O2 rare earth zirconium manganese composite oxide was mixed to 1:0.5:0.5:5 to obtain a mixed solution with a concentration of 1.5M. Under stirring conditions, the mixed material liquid was added at a constant rate to a 2.9M NaOH solution, the pH during precipitation was 8-14, the final pH value was 8, the temperature was controlled at 60°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 800°C for 7h to obtain a rare earth zirconium oxide. The rare earth zirconium oxide was mixed with a 4.1M Ce-containing Mn(CH3COO)2 solution, heat-treated at 200°C for 5h, and further roasted at 820°C for 9h to obtain a rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.2 Nd 0.05 S 0.05 Mn 0.2 Zr 0.5 Got O2.

[0056] The maximum conversion rate of NO oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 63%, and the conversion temperature corresponding to the maximum conversion rate was 296°C.

[0057] Example 5 Ce 0.05 Nd 0.05 Y 0.05 Al 0.1 Mn 0.2 Zr 0.7 The molar ratio of Ce / Nd / Y / Al / Zr in the O2 rare earth zirconium manganese composite oxide was mixed to 0.2:0.3:0.5:1:7 to obtain a mixed solution with a concentration of 1.6M. Under stirring conditions, the mixed material liquid and 3.6M ammonia aqueous solution were added at a constant rate into the reactor, the pH during precipitation was controlled to 10±0.2, the end pH value was 10.2, the temperature was controlled at 50°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 700°C for 5h to obtain rare earth zirconium oxide. The rare earth zirconium oxide was mixed with 4.3M Ce, Nd-containing Mn(NO3)2 solution, followed by heat treatment at 200°C for 5h and roasting at 600°C for 5h to obtain rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.05 Nd 0.05Y 0.05 Al 0.1 Mn 0.2 Zr 0.7 Got O2.

[0058] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 66%, and the conversion temperature corresponding to the maximum conversion rate was 289°C.

[0059] Example 6 Ce 0.14 La 0.03 Nd 0.04 Y 0.05 Mn 0.16 Zr 0.58 The molar ratio of Ce / La / Nd / Y / Zr in the O2 rare earth zirconium manganese composite oxide was mixed to 5:2:3:5:58 to obtain a mixed solution with a concentration of 1.5M. Under stirring conditions, the mixed material liquid was added at a constant rate to a 2.1M NaOH solution, the pH during precipitation was 8-11, the final pH value was 8, the temperature was controlled at 40°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 700°C for 6 hours to obtain a rare earth zirconium oxide. The rare earth zirconium oxide was mixed with a 4.6M Mn(NO3)2 solution containing Ce, La and Nd, and then heat-treated at 200°C for 13 hours and further roasted at 750°C for 10 hours to obtain the rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.14 La 0.03 Nd 0.04 Y 0.05 Mn 0.16 Zr 0.58 Got O2.

[0060] The maximum conversion rate of NO oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 70%, and the conversion temperature corresponding to the maximum conversion rate was 280°C.

[0061] Example 7 Ce 0.4 Nd 0.05 Hf 0.05 Mn 0.2 Zr 0.3The molar ratio of Ce / Nd / Hf / Zr in the O2 rare earth zirconium manganese composite oxide was mixed to 3:0.5:0.5:3 to obtain a mixed solution with a concentration of 1.5M. Under stirring conditions, 2.6M NaOH solution was added to the mixed material liquid at a constant speed, the pH during precipitation was 5-10, the final pH value was 10, the temperature was controlled at 60°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 800°C for 7 hours to obtain rare earth zirconium oxide. The rare earth zirconium oxide was mixed with a 4.9M Ce-containing Mn(CH3COO)2 solution, and then heat-treated at 210°C for 7 hours and roasted at 750°C for 9 hours to obtain rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.4 Nd 0.05 Hf 0.05 Mn 0.2 Zr 0.5 Got O2.

[0062] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 64%, and the conversion temperature corresponding to the maximum conversion rate was 292°C.

[0063] Example 8 Ce 0.4 La 0.02 Nd 0.05 Y 0.03 Mn 0.2 Zr 0.3 The molar ratio of Ce / La / Nd / Y / Zr in the O2 rare earth zirconium manganese composite oxide was mixed to 3:0.2:0.5:0.3:3 to obtain a mixed solution with a concentration of 1.6M. Under stirring conditions, the mixed material liquid was added at a constant rate to a 2.8M ammonium bicarbonate solution, the pH during precipitation was 8±1, the final pH value was 9.4, the temperature was controlled at 50°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 800°C for 7h to obtain a rare earth zirconium oxide. The rare earth zirconium oxide was mixed with a 4.4M Ce-containing Mn(NO3)2 solution, followed by heat treatment at 200°C for 9h and further roasting at 750°C for 10h to obtain a rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.4 La 0.02 Nd0.05 Y 0.03 Mn 0.2 Zr 0.3 Got O2.

[0064] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 62%, and the conversion temperature corresponding to the maximum conversion rate was 299°C.

[0065] Example 9 Ce 0.2 Sm 0.2 La 0.02 Nd 0.05 Y 0.03 Mn 0.3 Zr 0.2 O 1.9 The molar ratio of Ce / Sm / La / Nd / Y / Zr in the rare earth zirconium manganese composite oxide was 1:1:0.2:0.5:0.3:2 to obtain a mixed solution with a concentration of 1.4M. Under stirring conditions, the mixed material liquid and 2.6M NaOH solution were added at a constant rate into the reactor, the pH during precipitation was 8.5±0.5, the pH value at the end was 9, the temperature was controlled at 50°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 700°C for 5 hours to obtain a rare earth zirconium oxide. The rare earth zirconium oxide was mixed with a 5.1M Ce, Sm-containing Mn(NO3)2 solution, heat-treated at 300°C for 7 hours, and further roasted at 600°C for 9 hours to obtain a rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.2 Sm 0.2 La 0.02 Nd 0.05 Y 0.03 Mn 0.3 Zr 0.2 O 1.9 obtained.

[0066] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 59%, and the conversion temperature corresponding to the maximum conversion rate was 310°C.

[0067] Example 10 Ce 0.1 Mn0.15 Fe 0.05 Zr 0.7 The molar ratio of Ce / Zr in the O2 rare earth zirconium manganese composite oxide was mixed to 0.5:7 to obtain a mixed solution with a concentration of 1.5M. Under stirring conditions, the mixed material liquid and 1.2M ammonia aqueous solution were added to the reactor at a constant rate, the pH during precipitation was 7±0.2, the final pH value was 9, the temperature was controlled at 50°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 600°C for 6 hours to obtain rare earth zirconium oxide. The rare earth zirconium oxide was mixed with 3.8M Ce-containing MnCl2, FeCl3 solution, followed by heat treatment at 150°C for 6 hours and further roasting at 500°C for 10 hours to obtain rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.1 Mn 0.15 Fe 0.05 Zr 0.7 Got O2.

[0068] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 65%, and the conversion temperature corresponding to the maximum conversion rate was 283°C.

[0069] Example 11 Ce 0.3 Mn 0.1 Fe 0.05 Co 0.05 Zr 0.5 The molar ratio of Ce / Zr in the O2 rare earth zirconium manganese composite oxide was mixed to 2:5 to obtain a mixed solution with a concentration of 1.2M. Under stirring conditions, the mixed material liquid was added at a constant rate to a 2.1M NaOH solution, the pH during precipitation was 8-14, the final pH value was 9, the temperature was controlled at 50°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 800°C for 7h to obtain a rare earth zirconium oxide. The rare earth zirconium oxide was mixed with a 4.4M Ce-containing Mn(CH3COO)2, Co(CH3COO)2 and Fe(CH3COO)2 solution, followed by heat treatment at 200°C for 6h and further roasting at 750°C for 8h to obtain a rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.3 Mn0.1 Fe 0.05 Co 0.05 Zr 0.5 Got O2.

[0070] The maximum conversion rate of NO oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 70%, and the conversion temperature corresponding to the maximum conversion rate was 280°C.

[0071] Example 12 Ce 0.3 Mn 0.1 Cu 0.05 Ti 0.05 Zr 0.5 The molar ratio of Ce / Zr in the O2 rare earth zirconium manganese composite oxide was mixed to be 2:5 to obtain a mixed solution with a concentration of 1.4M. Under stirring conditions, 1.8M NaOH solution was added to the mixed material liquid at a constant speed, the pH during precipitation was 8-11, the final pH value was 10, the temperature was controlled at 55°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 600°C for 6h to obtain a rare earth zirconium oxide. The rare earth zirconium oxide was mixed with a 5.2M Ce-containing Mn(NO3)2, Cu(NO3)2 and Ti(NO3)4 solution, followed by heat treatment at 150°C for 8h and further roasting at 800°C for 5h. After roasting, a rare earth manganese oxide containing a spinel structure was formed on the surface and grain boundaries of the rare earth zirconium oxide, and the rare earth manganese zirconium composite compound Ce doped on the grain boundaries and surface was formed. 0.3 Mn 0.1 Cu 0.05 Ti 0.05 Zr 0.5 Got O2.

[0072] The maximum conversion rate of NO oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 68%, and the conversion temperature corresponding to the maximum conversion rate was 281°C.

[0073] Example 13 Ce 0.2 La 0.05 Pr 0.05 Mn 0.1 Fe0.1 Zr 0.5 The molar ratio of Ce / La / Pr / Zr in the O2 rare earth zirconium manganese composite oxide was mixed to 1:0.3:0.5:5 to obtain a mixed solution with a concentration of 1.4M. Under stirring conditions, the mixed material liquid and 2.8M NaOH solution were added at a constant rate into the reactor, the pH during precipitation was controlled to 9±0.2, the end pH value was 10.7, the temperature was controlled at 40°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 800°C for 5h to obtain rare earth zirconium oxide. The rare earth zirconium oxide was mixed with 4.5M Ce, La-containing Mn(NO3)2, Fe(NO3)3 solution, followed by heat treatment at 200°C for 10h and further roasting at 600°C for 9h to obtain rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.2 La 0.05 Pr 0.05 Mn 0.1 Fe 0.1 Zr 0.5 Got O2.

[0074] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 70%, and the conversion temperature corresponding to the maximum conversion rate was 278°C.

[0075] Example 14 Ce 0.4 Nd 0.05 Mn 0.2 Fe 0.1 Sn 0.05 Zr 0.2The molar ratio of Ce / Nd / Zr in the O2 rare earth zirconium manganese composite oxide was mixed to 1:0.5:2 to obtain a mixed solution with a concentration of 1.6M. Under stirring conditions, the mixed material liquid was added at a constant rate to a 3.4M ammonium bicarbonate solution, the pH during precipitation was 9-10, the final pH value was 9, the temperature was controlled at 40°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 600°C for 4h to obtain a rare earth zirconium oxide. The rare earth zirconium oxide was mixed with a 3.8M Ce-containing MnCl2, FeCl3 and SnCl4 solution, followed by heat treatment at 250°C for 5h and further roasting at 800°C for 7h. After roasting, a rare earth manganese oxide with a mullite structure was formed on the surface and grain boundaries of the rare earth zirconium oxide, and the rare earth manganese zirconium composite compound Ce doped on the grain boundaries and surface was formed. 0.4 Nd 0.05 Mn 0.2 Fe 0.1 Sn 0.05 Zr 0.2 Got O2.

[0076] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 72%, and the conversion temperature corresponding to the maximum conversion rate was 268°C.

[0077] Example 15 Ce 0.2 Sm 0.2 La 0.02 Nd 0.05 Y 0.03 Mn 0.1 Co 0.1 Zr 0.3The molar ratio of Ce / Sm / La / Nd / Y / Zr in the O2 rare earth zirconium manganese composite oxide was mixed to 1:1:0.2:0.5:0.3:3 to obtain a mixed solution with a concentration of 1.4M. Under stirring conditions, the mixed material liquid and 2.7M NaOH solution were added at a constant rate into the reactor, the pH during precipitation was controlled to 8±0.2, the final pH value was 9.4, the temperature was controlled at 50°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 800°C for 4h to obtain rare earth zirconium oxide. The rare earth zirconium oxide was mixed with 4.6M Ce, Sm-containing Mn(NO3)2, Co(NO3)2 solution, followed by heat treatment at 100°C for 11h and further roasting at 600°C for 9h to obtain rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.2 Sm 0.2 La 0.02 Nd 0.05 Y 0.03 Mn 0.3 Zr 0.2 O 1.9 obtained.

[0078] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 74%, and the conversion temperature corresponding to the maximum conversion rate was 264°C.

[0079] Example 16 Ce 0.2 S 0.1 Mn 0.15 W 0.05 Zr 0.5The molar ratio of Ce / Si / Zr in the O2 rare earth zirconium manganese composite oxide was mixed to be 1:1:5 to obtain a mixed solution with a concentration of 1.2M. Under stirring conditions, the mixed material liquid was added at a constant rate to a 2.2M NaOH solution, the pH during precipitation was 9-14, the final pH value was 9, the temperature was controlled at 30°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 750°C for 5 hours to obtain a rare earth zirconium oxide. The rare earth zirconium oxide was mixed with a 4.4M Ce-containing Mn(CH3COO)2, hexacarbonyl tungsten solution, followed by heat treatment at 150°C for 7 hours and further roasting at 800°C for 7 hours to obtain a rare earth manganese zirconium composite compound doped with Ce on the grain boundary and surface. 0.2 S 0.1 Mn 0.15 W 0.05 Zr 0.5 Got O2.

[0080] The maximum conversion rate of NO oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 76%, and the conversion temperature corresponding to the maximum conversion rate was 246°C.

[0081] (Example 17) Ce 0.1 Nd 0.05 Y 0.05 Mn 0.15 Cu 0.15 Zr 0.5 The molar ratio of Ce / Nd / Y / Zr in the O2 rare earth zirconium manganese composite oxide was mixed to 1:1:1:10 to obtain a mixed solution with a concentration of 1.4M. Under stirring conditions, the mixed material liquid was added to a 1.9M urea solution at a constant speed, the pH during precipitation was 8-10, the final pH value was 8, the temperature was controlled at 100°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 850°C for 4h to obtain a rare earth zirconium oxide. The rare earth zirconium oxide was mixed with a 4.2M Ce-containing Mn(NO3)2, Cu(NO3)2 solution, followed by heat treatment at 200°C for 7h and further roasting at 750°C for 6h to obtain a rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.2 Nd 0.05 Hf0.05 Mn 0.1 Nb 0.1 Zr 0.5 Got O2.

[0082] The maximum conversion rate of NOx produced by the rare earth manganese zirconium composite compound catalyst according to the present embodiment of the present invention is 78%, and the corresponding conversion temperature is 240°C. After aging at a high temperature of 850°C for 15h, the maximum conversion rate of NOx is 70%, and the corresponding conversion temperature is 250°C.

[0083] (Example 18) Ce 0.2 Al 0.1 Mn 0.05 Cr 0.1 Zr 0.55 The molar ratio of Ce / Al / Zr in the O2 rare earth zirconium manganese composite oxide was mixed to 1:1:5.5 to obtain a mixed solution with a concentration of 1.5M. Under stirring conditions, the mixed material liquid and 3.2M NaOH solution were added at a constant rate into the reactor, the pH during precipitation was controlled to 9±0.2, the final pH value was 9.5, and the temperature was controlled at 45°C. The precipitate was filtered, washed and dried, and the dried product was roasted at 700°C for 6 hours to obtain rare earth zirconium oxide. The rare earth zirconium oxide was mixed with 4.6M Ce-containing Mn(NO3)2, Cr(NO3)3 solution, and then heat-treated at 200°C for 6 hours and roasted at 900°C for 3 hours to obtain rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.2 Al 0.1 Mn 0.05 Cr 0.1 Zr 0.55 Got O2.

[0084] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 74%, and the conversion temperature corresponding to the maximum conversion rate was 249°C.

[0085] (Example 19) Ce 0.1 Al 0.1 Mn 0.1 Zinc0.1 Zr 0.6 The molar ratio of Ce / Al / Zr in the O2 rare earth zirconium manganese composite oxide was mixed to be 0.5:1:6 to obtain a mixed solution with a concentration of 1.4M. Under stirring conditions, 2.6M NaOH solution was added to the mixed material liquid at a constant rate, the pH during precipitation was 5-9, the final pH value was 9, the temperature was controlled at 40°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 650°C for 8 hours to obtain rare earth zirconium oxide. The rare earth zirconium oxide was mixed with 4.7M Ce-containing MnCl2, ZnCl2 solution, followed by heat treatment at 150°C for 8 hours and further roasting at 800°C for 8 hours to obtain rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.1 Al 0.1 Mn 0.1 Zinc 0.1 Zr 0.6 Got O2.

[0086] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 72%, and the conversion temperature corresponding to the maximum conversion rate was 267°C.

[0087] (Example 20) Ce 0.15 La 0.05 Y 0.05 Al 0.05 Mn 0.2 Zr 0.5 O 1.98 P 0.01The molar ratio of Ce / La / Y / Al / Zr in the rare earth zirconium manganese composite oxide was mixed to 2:1:1:1:10 to obtain a mixed solution with a concentration of 1.0M. Under stirring conditions, the mixed material liquid was added at a constant rate to a 3.2M ammonia aqueous solution, the pH during precipitation was 8-10, the final pH value was 8, the temperature was controlled at 40°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 800°C for 5 hours to obtain a rare earth zirconium oxide. The rare earth zirconium oxide was mixed with a 4.7M Ce-containing MnCl2, H3PO4 solution, followed by heat treatment at 200°C for 7 hours and further roasting at 750°C for 7 hours to obtain a rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.15 La 0.05 Y 0.05 Al 0.05 Mn 0.2 Zr 0.5 O 1.98 P 0.01 obtained.

[0088] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 67%, and the conversion temperature corresponding to the maximum conversion rate was 279°C.

[0089] Example 21 Ce 0.15 Mn 0.2 Ni 0.15 Zr 0.5 O 1.98 S 0.02 The molar ratio of Ce / Zr in the rare earth zirconium manganese composite oxide was 0.2:1 to obtain a mixed solution with a concentration of 1.2M. Under stirring conditions, the mixed material liquid and 2.6M NaOH solution were added at a constant rate into the reactor, the pH during precipitation was 9±0.2, the final pH value was 10.4, the temperature was controlled at 40°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 800°C for 6 hours to obtain a rare earth zirconium oxide. The rare earth zirconium oxide was mixed with 3.9M Ce-containing MnCl2, NiCl2 and dilute sulfuric acid solution, followed by heat treatment at 200°C for 6 hours and further roasting at 600°C for 10 hours to obtain a rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface.0.15 Mn 0.2 Ni 0.15 Zr 0.5 O 1.98 S 0.02 obtained.

[0090] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 72%, and the conversion temperature corresponding to the maximum conversion rate was 268°C.

[0091] Example 22 Ce 0.2 Mn 0.2 Cu 0.1 Zr 0.5 O 1.98 N 0.01 The rare earth zirconium manganese composite oxide was mixed so that the molar ratio of Ce / Zr was 1:5, and the concentration of Ce was 0.5M. 3+ and Zr 4+ The mixed solution was obtained, and the mixed material liquid was added to a 3.1M aqueous ammonia solution at a constant speed under stirring conditions. The pH during precipitation was 9-11, and the final pH value was 9. The temperature was controlled at 40°C. The precipitate was filtered, washed, and dried, and the dried product was roasted at 600°C for 9 hours to obtain rare earth zirconium oxide. The rare earth zirconium oxide was mixed with 4.2M Ce-containing MnSO4, CuSO4, and pyridine nitrogen solution, followed by heat treatment at 150°C for 8 hours and further roasting at 900°C for 9 hours to obtain rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.2 Mn 0.2 Cu 0.1 Zr 0.5 O 1.98 N 0.01 obtained.

[0092] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 64%, and the conversion temperature corresponding to the maximum conversion rate was 295°C.

[0093] Example 23 Ce 0.14 La 0.03 Nd 0.04 Y0.05 Mn 0.16 Zr 0.58 O 1.98 F 0.04 The molar ratio of Ce / La / Nd / Y / Zr in the rare earth zirconium manganese composite oxide was mixed to 6:2:4:3:58 to obtain a mixed solution with a concentration of 1.5M. Under stirring conditions, the mixed material liquid was added at a constant rate to a 2.7M NaOH solution, the pH during precipitation was 8-13, the final pH value was 8, the temperature was controlled at 80°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 650°C for 7 hours to obtain a rare earth zirconium oxide. The rare earth zirconium oxide was mixed with a 4.8M Mn(NO3)2 solution and a NH4F solution containing Ce, La, and Y, and then heat-treated at 200°C for 6 hours and further roasted at 800°C for 11 hours to obtain a rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.14 La 0.03 Nd 0.04 Y 0.05 Mn 0.16 Zr 0.58 O 1.98 F 0.04 obtained.

[0094] The maximum conversion rate of NO oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 68%, and the conversion temperature corresponding to the maximum conversion rate was 283°C.

[0095] Example 24 Ce 0.15 La 0.04 Nd 0.04 Y 0.06 Mn 0.16 Zr 0.55The molar ratio of Ce / La / Nd / Y / Zr in the O2 rare earth zirconium manganese composite oxide was 10:3:4:6:55, and the mixture was dissolved in water to obtain a mixed solution with a concentration of 1.5M. Under stirring conditions, the mixed liquid was added at a constant speed to a 2.1M ammonia aqueous solution, the pH during precipitation was 8-10, and the final pH value was 10.1. The temperature was controlled at 40°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 800°C for 6h to obtain a rare earth zirconium oxide. The rare earth zirconium oxide was mixed with a 4.8M MnCl2 solution containing Ce and La and heat-treated at 200°C for 6 hours. The heat-treated product was washed, dried, heat-treated at 250°C for 5 hours, and then roasted at 800°C for 6 hours. After the roasting, rare earth manganese oxide containing a perovskite structure was formed on the surface and grain boundaries of the rare earth zirconium oxide, and rare earth manganese zirconium complex compound Ce doped on the grain boundaries and surface was formed. 0.15 La 0.04 Nd 0.04 Y 0.06 Mn 0.16 Zr 0.55 Got O2.

[0096] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 71%, and the conversion temperature corresponding to the maximum conversion rate was 279°C.

[0097] (Example 25) Ce 0.15 Nd 0.05 Mn 0.05 V 0.05 Sn 0.05 Zr 0.65The Ce / Nd / Zr molar ratio in the O2 rare earth zirconium manganese composite oxide was dissolved and mixed in water to obtain a mixed solution with a concentration of 1.5M. Under stirring conditions, 2.5M ammonia aqueous solution was added to the mixed material liquid at a constant speed, the pH during precipitation was 5-11, the final pH value was 11, the temperature was controlled at 50°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 700°C for 6h to obtain rare earth zirconium oxide. The rare earth zirconium oxide was mixed with 4.8M Ce-containing Mn(CH3COO)2, Sn(CH3COO)4 and VCl3 solution, and then heat-treated at 180°C for 15h and roasted at 500°C for 4h. The roasted product was crushed and roasted at 800°C for 4h to obtain rare earth manganese zirconium composite compound Ce with a core-shell structure. 0.15 Nd 0.05 Mn 0.05 V 0.05 Sn 0.05 Zr 0.65 Got O2.

[0098] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst having a core-shell structure obtained by the manufacturing method of this embodiment of the present invention was 65%, and the conversion temperature corresponding to the maximum conversion rate was 290°C.

[0099] (Example 26) Ce 0.15 Nd 0.05 Pr 0.05 EU 0.05 Mn 0.2 Zr 0.5 O 1.98 S 0.02The molar ratio of Ce / Nd / Pr / Eu / Zr in the rare earth zirconium manganese composite oxide was mixed to 2:1:1:1:10 to obtain a mixed solution with a concentration of 1.5M. Under stirring conditions, the mixed solution and 2.2M ammonium bicarbonate solution were added to the reactor at a constant rate, the pH during precipitation was controlled to 8±0.2, the end pH value was 10, and the temperature was controlled to 44°C. The precipitate was filtered, washed and dried, and the dried product was roasted at 600°C for 8 hours to obtain a rare earth zirconium oxide. The rare earth zirconium oxide was mixed with a 4.5M Ce-containing manganese sulfate solution, and then heat-treated at 280°C for 7 hours and roasted at 650°C for 3 hours. The roasted product was crushed and roasted at 700°C for 10 hours to obtain a rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.15 Nd 0.05 Pr 0.05 EU 0.05 Mn 0.2 Zr 0.5 O 1.98 S 0.02 obtained.

[0100] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 64%, and the conversion temperature corresponding to the maximum conversion rate was 291°C.

[0101] Example 27 Ce 0.4 Sc 0.02 Yb 0.05 Y 0.03 Mn 0.1 Ti 0.1 Zr 0.3 O 1.98 S 0.02The molar ratio of Ce / Sc / Yb / Y / Zr in the rare earth zirconium manganese composite oxide was 25:2:5:3:30 to obtain a mixed solution with a concentration of 1.5M. Under stirring conditions, the mixed solution and 2.2M ammonia aqueous solution were added at a constant rate into the reactor, the pH during precipitation was controlled to 9.5±0.2, the final pH value was 10, and the temperature was controlled to 40°C. The precipitate was filtered, washed, and dried, and the dried product was roasted at 550°C for 10 hours to obtain a rare earth zirconium oxide. The rare earth zirconium oxide was mixed with a 4.4M Ce-containing manganese sulfate and titanyl sulfate solution, and then heat-treated at 180°C for 8 hours and roasted at 450°C for 10 hours. The roasted product was crushed and roasted at 650°C for 10 hours to obtain a rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.4 Sc 0.02 Yb 0.05 Y 0.03 Mn 0.1 Ti 0.1 Zr 0.3 O 1.98 S 0.02 obtained.

[0102] The maximum conversion rate of NO oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 67%, and the conversion temperature corresponding to the maximum conversion rate was 280°C.

[0103] (Example 28) Ce 0.2 Nd 0.05 Tm 0.05 Mn 0.1 Zinc 0.1 Zr 0.5The molar ratio of Ce / Nd / Tm / Zr in the O2 rare earth zirconium manganese composite oxide was 3:1:1:10, dissolved and mixed in water to obtain a mixed solution with a concentration of 1.5M. Under stirring conditions, the mixed material liquid was added to 2.1M ammonia water at a constant speed, the pH during precipitation was 8-11, the final pH value was 10.5, the temperature was controlled at 55°C, the precipitate was filtered, washed and dried, and the dried product was roasted at 800°C for 2 hours to obtain rare earth zirconium oxide. The rare earth zirconium oxide was mixed with 4.6M Ce-containing Mn(NO3)2, Zn(NO3)2 solution, and then heat-treated at 280°C for 6 hours and roasted at 850°C for 11 hours to obtain rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.2 Nd 0.05 Tm 0.05 Mn 0.1 Zinc 0.1 Zr 0.5 Got O2.

[0104] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 63%, and the conversion temperature corresponding to the maximum conversion rate was 290°C.

[0105] (Example 29) Ce 0.14 La 0.03 Gd 0.04 Ho 0.05 Mn 0.15 Cr 0.5 Zr 0.58The molar ratio of Ce / La / Gd / Ho / Zr in the O2 rare earth zirconium manganese composite oxide was 10:2:4:5:58, and the mixture solution with a concentration of 1.5M was dissolved and mixed in water. Under stirring conditions, the mixture liquid was added at a constant rate to a 2.1M ammonium bicarbonate solution, the pH during precipitation was 9-11, and the final pH value was 9. The temperature was controlled at 60°C, the precipitate was filtered, washed, and dried, and the dried product was roasted at 800°C for 4 hours to obtain a rare earth zirconium oxide. The rare earth zirconium oxide was mixed with a 4.7M Ce, La-containing Mn(NO3)2 solution, and then heat-treated at 150°C for 10 hours and roasted at 680°C for 12 hours to obtain a rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.14 La 0.03 Gd 0.04 Ho 0.05 Mn 0.15 Cr 0.5 Zr 0.58 Got O2.

[0106] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 63%, and the conversion temperature corresponding to the maximum conversion rate was 291°C.

[0107] (Example 30) Ce 0.14 EU 0.03 Al 0.04 S 0.05 Mn 0.16 Zr 0.58 O 1.98 N 0.02The molar ratio of Ce / Eu / Al / Si / Zr in the rare earth zirconium manganese composite oxide was mixed to 12:2:4:5:58 to obtain a mixed solution with a concentration of 1.5M. Under stirring conditions, the mixed material liquid was added at a constant rate to a 2.1M NaOH solution, the pH during precipitation was 8-11, the final pH value was 8, and the temperature was controlled at 90°C. The precipitate was filtered, washed, and dried, and the dried product was roasted at 760°C for 8 hours to obtain a rare earth zirconium oxide. The rare earth zirconium oxide was mixed with a 4.2M Ce, Eu-containing Mn(NO3)2 solution, and then heat-treated at 200°C for 7 hours and further roasted at 500°C for 13 hours to obtain a rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.14 EU 0.03 Al 0.04 S 0.05 Mn 0.16 Zr 0.58 Got O2.

[0108] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 60%, and the conversion temperature corresponding to the maximum conversion rate was 292°C.

[0109] (Example 31) Ce 0.3 La 0.05 Mn 0.1 Fe 0.05 Zr 0.5The molar ratio of Ce / La / Zr in the O2 rare earth zirconium manganese composite oxide was mixed to be 1:0.5:5, and a mixed solution with a concentration of 1.4M was obtained. Under stirring conditions, 1.8M NaOH solution was added into the mixed material liquid at a constant rate, and a certain amount of cerium nitrate solution was added in the precipitation process, and then precipitation was continued to completely precipitate all cations. The pH during precipitation was 8-11, and the end pH value was 10. The temperature was controlled at 55°C, and the precipitate was filtered, washed and dried. The dried product was roasted at 700°C for 6h to obtain rare earth zirconium oxide with element gradient distribution. The rare earth zirconium oxide was mixed with 5.2M Ce-containing Mn(NO3)2, Fe(NO3)2 solution, followed by heat treatment at 150°C for 8h and further roasting at 700°C for 5h to obtain rare earth manganese zirconium composite compound Ce doped on the grain boundary and surface. 0.3 Mn 0.1 Cu 0.05 Ti 0.05 Zr 0.5 Got O2.

[0110] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 73%, and the conversion temperature corresponding to the maximum conversion rate was 277°C.

[0111] Example 32 Ce 0.15 Nd 0.05 EU 0.05 Mg 0.15 Mn 0.2 Zr 0.4In the O2 rare earth zirconium manganese composite oxide, Ce / Nd / Eu / Zr with a molar ratio of 2:1:1:10 was dissolved and mixed in water to obtain a mixed solution with a concentration of 1.3M. Under stirring conditions, the mixed solution and 2.5M magnesium bicarbonate solution were added at a constant rate into the reactor, the pH during precipitation was controlled at 7.5±0.2, the final pH value was 9, and the temperature was controlled at 55°C. The precipitate was filtered, washed and dried, and the dried product was roasted at 800°C for 8h to obtain rare earth zirconium oxide. The rare earth zirconium oxide was mixed with a 4M Ce-containing Mn(NO3)3 solution, and then heat-treated at 200°C for 5 hours, heated to 250°C for 8 hours, roasted at 500°C for 4 hours, and then roasted at 750°C for 8 hours. The roasted product was pulverized to obtain a rare earth manganese zirconium composite compound Ce with a core-shell structure. 0.15 Nd 0.05 EU 0.05 Mg 0.15 Mn 0.2 Zr 0.4 Got O2.

[0112] The maximum conversion rate of NOx oxidized by the rare earth manganese zirconium composite compound catalyst having a core-shell structure obtained by the manufacturing method of this embodiment of the present invention was 70%, and the conversion temperature corresponding to the maximum conversion rate was 286°C.

[0113] (Example 33) Ce 0.2 Sm 0.2 La 0.02 Ga 0.05 Ca 0.03 Mn 0.1 Co 0.1 Zr 0.3 O 1.98 S 0.02The Ce / Ga / Ca / Zr nitrates with a molar ratio of 10:5:3:30 in the rare earth zirconium manganese composite oxide are dissolved and mixed in water to obtain a mixed solution with a concentration of 1.1M. Under stirring conditions, the mixed solution and 2.5M sodium hydroxide solution are added at a constant rate into the reactor, the pH during precipitation is controlled at 8±0.2, the end pH value is 13, and the temperature is controlled at 55°C. Then, the required Sm(NO3)3, La(NO3)3 solution and sodium hydroxide solution are used to carry out the second stage precipitation reaction, the end pH value of the precipitation is 10, the precipitate is filtered, washed and other post-treatments are carried out on the precipitated material, and the dried product is roasted at 700°C for 11h to obtain a gradient distribution rare earth zirconium oxide. The rare earth zirconium oxide was mixed with a 4M Ce-containing Mn(NO3)3 solution, and then heat-treated at 300°C for 6 hours and then roasted at 800°C for 10 hours. The roasted product was then pulverized to obtain a rare earth manganese zirconium composite compound Ce with a core-shell structure. 0.2 Sm 0.2 La 0.02 Ga 0.05 Ca 0.03 Mn 0.1 Co 0.1 Zr 0.3 O 1.98 S 0.02 obtained.

[0114] The maximum conversion rate of NOx oxidized by the gradient distribution rare earth manganese zirconium composite compound catalyst obtained by the manufacturing method of this embodiment of the present invention was 71%, and the conversion temperature corresponding to the maximum conversion rate was 284°C.

[0115] (Example 34) Ce 0.2 La 0.05 Y 0.05 Mn 0.2 Zr 0.5The Ce / La / Y / Z / chloride salt with a molar ratio of 2:1:1:10 in the O2 rare earth zirconium manganese composite oxide is dissolved and mixed with water to obtain a mixed solution with a concentration of 1.3M. The mixed material liquid is mixed with 2.5mol / L sodium hydroxide solution to carry out a precipitation reaction. The precipitation temperature is 60℃, and the pH value during precipitation is controlled to 5-11. The pH value is adjusted twice to carry out stepwise precipitation. First, the pH value is adjusted to 5 to precipitate zirconium ions, and then the pH value is gradually adjusted to 11 to precipitate cerium ions and yttrium ions. The pH value at the end of the precipitation is 11. The precipitate is filtered, washed and dried. The dried product is roasted at 750℃ for 8h to obtain a rare earth zirconium oxide with a gradient distribution. The rare earth zirconium oxide was mixed with a 4M Ce-containing Mn(NO3)3 solution, and then heat-treated at 200°C for 9 hours, roasted at 500°C for 4 hours, and then roasted at 800°C for 6 hours. The roasted product was then pulverized to obtain a rare earth manganese zirconium composite compound Ce with gradient distribution and core-shell structure. 0.2 La 0.05 Y 0.05 Mn 0.2 Zr 0.5 Got O2.

[0116] The rare earth manganese zirconium composite catalyst with gradient distribution and core-shell structure obtained by the preparation method of this embodiment of the present invention has a maximum NO conversion of 68%, and the corresponding conversion temperature is 288°C. After aging at a high temperature of 900°C for 15h, the maximum NO conversion is 60%, and the corresponding conversion temperature is 292°C.

[0117] (Example 35) Ce 0.25 La 0.05 Mn 0.35 Nd 0.05 Zr 0.3 O 1.98The Ce / Zr nitrate with a molar ratio of 1:2 in the rare earth zirconium manganese composite oxide is dissolved and mixed with water to obtain a mixed solution with a concentration of 1.3M. The mixed material liquid is mixed with 2.5 mol / L ammonia aqueous solution to carry out a precipitation reaction. The precipitation temperature is 80°C, and the pH value during the precipitation is controlled to 9-11. The precipitation is carried out in two stages. First, the pH value is adjusted to 5 to precipitate zirconium ions, and after aging for 1 hour, the pH value is further gradually adjusted to 11 to precipitate cerium ions. The pH value at the end of the precipitation is 11. The precipitate is filtered, washed and dried, and the dried product is roasted at 600°C for 10 hours to obtain a rare earth zirconium oxide with a core-shell structure. The rare earth zirconium oxide was mixed with a 3.6M Ce-containing Mn(NO3)3 solution, and then heat-treated at 170°C for 12 hours, roasted at 550°C for 2 hours, and then roasted at 600°C for 10 hours. The roasted product was pulverized to obtain a rare earth manganese zirconium composite compound Ce with a core-shell structure. 0.25 La 0.05 Mn 0.35 Nd 0.05 Zr 0.3 O 1.98 obtained.

[0118] The rare earth manganese zirconium composite compound catalyst with gradient distribution and core-shell structure obtained by the preparation method of this embodiment of the present invention has a maximum NO conversion of 73%, and the conversion temperature corresponding to the maximum conversion is 265°C.

[0119] As can be seen from the data of the above comparative examples and examples, the conversion rate of the product NO prepared by the preparation methods provided in the comparative examples is less than 50% and the conversion temperatures are all 350°C, while the maximum conversion rate of the rare earth manganese zirconium composite compound catalytic oxidation NO obtained by the preparation methods of the examples of the present invention is 78%, and the corresponding conversion temperature of the maximum conversion rate is 240°C. The conversion rate of NO is obviously improved, and the corresponding conversion temperature is obviously reduced, and an obvious beneficial technical effect is obtained.

[0120] In summary, the present invention relates to a rare earth manganese zirconium composite compound doped with grain boundaries and surfaces, its manufacturing method and application, and a rare earth manganese zirconium composite compound is obtained by forming a rare earth manganese oxide with a special structure on the grain boundaries and surfaces of rare earth zirconium oxide by grain boundary doping method. The oxygen vacancies on the grain boundaries and surfaces are increased, thereby increasing the amount of active oxygen and improving the catalytic activity of the rare earth manganese zirconium composite compound, suppressing its high-temperature sintering, and improving its ability to catalyze the oxidation of NO. The use of the rare earth manganese zirconium composite compound as a catalyst can greatly reduce the amount of precious metals used.

[0121] It should be understood that the above specific embodiments of the present invention are merely used to exemplarily explain or interpret the principles of the present invention, and are not intended to limit the present invention. Therefore, any modifications, equivalent replacements, improvements, etc. made without departing from the spirit and scope of the present invention should be included within the protection scope of the present invention. Furthermore, the claims of the present invention are intended to include all changes and modifications that are included within the scope and boundaries of the claims, or are equivalent to the scope and boundaries.

Claims

1. A rare earth manganese zirconium composite compound doped on grain boundaries and surfaces, the chemical formula of the rare earth manganese zirconium composite compound is RE a Mn b Zr c L d M e O (2-δ) D β where RE is a rare earth element, M and L are cationic doping elements, and D is an anionic doping element; Here, 0.1≦a≦0.5, 0.05≦b≦0.4, 0.2≦c≦0.8, 0≦d≦0.2, 0≦e≦0.2, 0≦δ≦0.1, 0≦β≦0.1, and a+b+c+d+e=1. A rare earth manganese zirconium composite compound doped at grain boundaries and surfaces.

2. The grain boundary and surface doped rare earth manganese zirconium composite compound according to claim 1, characterized in that the grain boundary and surface of the rare earth manganese zirconium composite compound contain one or more of doping elements M, L and D.

3. The rare earth manganese zirconium composite compound doped at the grain boundaries and surface according to claim 1 or 2, characterized in that the doping elements M, L and D are in the form of one or more of oxides, nitrogen-containing compounds, fluorine compounds, phosphates and sulfates at the grain boundaries and surface of the rare earth manganese zirconium composite oxide.

4. The RE includes one or a combination of one or more of La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y, and Sc; Preferably, RE is one or more of La, Ce, Pr, Nd, Sm, Eu, Gd and Y, the rare earth manganese zirconium composite compound doped on the grain boundary and surface according to any one of claims 1 to 3.

5. The doping element M of the cations comprises a transition metal, preferably one or more combinations of Fe, Co, Ni, Cu, Zn, V, Ti, Cr, Mo, W, Hf and Nb; the doping element L of the cations comprises one or more combinations of alkaline earth metals and Ga, Al, Si, Sn, preferably one or more combinations of alkaline earth metals Ba, Sr, Mg and Ca; and the doping element D comprises one or more combinations of anions N, P, F and S. The rare earth manganese zirconium composite compound doped at the grain boundary and surface according to any one of claims 1 to 4.

6. The rare earth manganese zirconium composite compound doped on the grain boundary and surface according to any one of claims 1 to 5, characterized in that the ratio of the total amount of +3 and +4 valences of Mn on the surface and grain boundary of the rare earth manganese zirconium composite compound to the total valence of Mn is greater than 80%, preferably greater than 90%.

7. The rare earth manganese zirconium composite compound according to any one of claims 1 to 6, characterized in that the rare earth manganese zirconium composite compound comprises a core-shell structure, the core comprises rare earth and zirconium elements, and the shell comprises rare earth and manganese elements.

8. The rare earth manganese zirconium composite compound according to any one of claims 1 to 6, characterized in that the rare earth manganese zirconium composite compound comprises rare earth zirconium oxide with element gradient distribution.

9. Step S1 of mixing an aqueous mixed salt solution of Zr and RE or an aqueous mixed salt solution of Zr, RE, L and D having a desired stoichiometric ratio with an alkaline solution, carrying out a precipitation reaction, and obtaining a rare earth zirconium-based oxide containing RE and L through filtration, washing, drying and roasting; Step S2 of mixing a mixed salt aqueous solution of Mn and RE or a mixed salt aqueous solution of Mn, RE, M and D having a desired stoichiometric ratio with the rare earth zirconium oxide obtained in step S1 to obtain a composite compound wet material; Step S3, performing one or two heat treatments on the composite compound moisturizing agent obtained in step S2; and step S4, which is a step of performing one or two post-sintering treatments on the material obtained in step S3 to obtain a rare earth manganese zirconium composite compound doped on the grain boundary and the surface.

10. The method according to claim 9, characterized in that the doping element D is added in one or two steps in steps S1 and S2, and the doping element D is added in the form of one or more combinations of nitrates, fluorine compounds, phosphates and sulfates, preferably one or more combinations of nitrates and sulfates.

11. The method according to claim 9, characterized in that the manganese source in the mixed salt solution in step S1 and step S2 comprises one or a combination of one or more of chlorides, nitrates, sulfates and acetates, preferably manganese nitrate, the zirconium source comprises one or a combination of one or more of oxychlorides, nitrates, sulfates, acetates and citrates, preferably zirconium oxynitrate, and the aqueous salt solutions of M, L and RE comprise one or a combination of one or more of chlorides, nitrates, sulfates, acetates, citrates and liquid salts of amino acids, and organosilicon compounds, preferably nitrates.

12. 10. The method according to claim 9, characterized in that the alkaline solution comprises at least one of magnesium bicarbonate, urea and hydroxides, carbonates or bicarbonates of at least one of the elements ammonium, sodium and potassium, preferably at least one of sodium hydroxide, urea, aqueous ammonia and ammonium bicarbonate.

13. The method according to claim 9, characterized in that in the precipitation process of step S1, the pH value is controlled at 4.5-14, preferably 5-11, the pH value at the end of precipitation is controlled at 8-13, preferably 9-11, and in the precipitation process, the temperature is 0-120°C, preferably 20-80°C.

14. The method according to claim 9, wherein the roasting conditions of the rare earth zirconium oxide are kept in the range of 500 to 1000 ° C for 1 to 20 hours, preferably in the range of 600 to 900 ° C for 2 to 10 hours.

15. The method according to claim 9, wherein the heat treatment temperature is 100-500°C and the time is 2-30h, preferably the heat treatment temperature is 150-300°C and the time is 6-12h.

16. The method according to claim 9, characterized in that the firing conditions are maintained in the range of 400 to 1000° C. for 1 to 20 hours, preferably in the range of 500 to 900° C. for 3 to 10 hours.

17. The method according to claim 9, characterized in that the particle size D50 of the post-treatment of the rare earth manganese zirconium complex compound is less than 15um, preferably less than 10um.

18. 10. The method according to claim 9, wherein a rare earth manganese oxide containing a perovskite, spinel or mullite structure is formed on the surface and grain boundaries of the rare earth zirconium oxide after firing.

19. 9. Use of the rare earth manganese zirconium composite compound doped on the grain boundary and surface according to any one of claims 1 to 8 in the fields of automobile exhaust gas purification, industrial exhaust gas treatment and catalytic combustion.

Citation Information

Patent Citations

  • Rare earth manganese / cerium zirconium composite compound with core-shell structure, preparation method and catalyst

    CN112439407A